EFFICIENCY OF IMPLEMENTING SIMPLE WATER FILTRATION TECHNOLOGY IN PARAN TONGA VILLAGE KECAMATAN SIMANGAMBAT SUB-DISTRICT, NORTH PADANG LAWAS UTARA DISTRICT - Arifandy, Muhammad Imam; Risuli, Muhammad; Tambak, Nurul Hidayah; Anggara, Rizki; Epril Lilawati, Tri Indah (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
The water problem in Parantonga Village is very worrying where the water conditions are murky, sandy and muddy. Plus the contamination of one of the closest water sources, namely the Barumun river. This condition makes people creative in creating simple water filter devices that can filter dirt. From the problems experienced by the community, they provide information about how much they need clean water. This research aims to become a source and voice the community’s difficulties so that it becomes a reference for the government in decision making. Making appropriate technological water filter equipment using several filter materials, namely coral, palm fiber and sand, has been proven to be able to purify water that was originally cloudy to become clear like rainwater and can be consumed physically as clean water. Having this tool makes it easier for the people of Parantonga village to get clean water and also prevents people from various dangerous diseases due to continuous consumption of dirty water. The research was carried out by conducting interviews as well as observations via online platforms and other data sources of information taken from various journals.